Technology Startups: The Case of South American Countries - Morales-Urrutia X.; Morales-Urrutia D.; Ávila-Herrera S. (My University, 2021)
The business environment has undergone major changes and is becoming increasingly competitive, a fact that has generated the emergence of new companies or startups as an alternative to the implementation of innovative, sustainable and profitable businesses over time, through the generation of alliances of different strategic actors existing in the environment. The data analyzed came from the Global Entrepreneurship Monitor for the period 2008-2014, the variables analyzed are: financing, education, policies, spending on R&D and innovation, technology parks and business incubators, the objective was to analyze the relationship of startups with environmental factors. The main results show that there is a close relationship with the factors analyzed, especially with financing, education and innovation. In conclusion, despite the fact that South American countries are lagging behind in economic and technological terms, there are certain signs of the generation of companies such as those analyzed in this study. © 2021, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.
Startups tecnológicas: El caso de países sudamericanos
Keywords: Innovation; Social Capital; Technology